Diagnostic Value of Sars-Cov-2 Antibody-Based Rapid Diagnostic Test in Paediatric Individuals Clinically Suspected of Covid-19 - Chand, Arun Bahadur; Bajracharya, Sohani; Amatya, Isha; Gurung, Parbati; Shrestha, Shila; Dulal, Maina; Dahal, Susheela; Pokhrel, Nayanum (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: The diagnosis of SARS-CoV-2 infection with quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR) has proven challenging in low and middle-income countries, including Nepal, due to its limited availability and higher costs. As such, a simple and cost-effective rapid diagnostic test based on the detection of SARS-CoV-2 antibodies could be an alternative for the diagnosis of individuals with COVID-19. Method: This study aimed to examine the diagnostic parameters of the SARS-CoV-2 antibody-based rapid diagnostic test (Ab-RDT) as well as the clinical and demographic characteristics of paediatric COVID-19 suspects. The pediatric individuals (<16 years) suspected of COVID-19 who had visited the hospital between January and June 2021 were subjected to the detection of the SARS-CoV-2 genome by qRT-PCR and the induction of antibodies (IgM/IgG) by the National Public Health Laboratory-approved Ab-RDT. The results of the diagnostic tests from the overall individuals and the demographic and clinical details from the individuals confirmed with COVID-19 were collected and analyzed using SPSS version 17.0, with statistical significance considered at p<0.05. Results: Among the total individuals (n=773), 193(24.98%) tested qRT-PCR-positive and 144(18.63%) tested Ab-RDT-positive. When measured against the gold standard qRT-PCR, Ab-RDT exhibits sensitivity of 74.6%, specificity of 99.7%, positive predictive value of 98.6%, and negative predictive value of 92.2% (p<0.001). Male sex (106/193) (p=0.023), the presence of multiple (≥3) symptoms (73/193) and (≥2) comorbidities (26/193), and a diagnosis of pneumonia (32/193) were identified as possible risk factors for SARS-CoV-2 infection. It seems that the low sensitivity of validated Ab-RDT could only complement qRT-PCR in the detection of SARS-CoV-2 antibodies Conclusion: It seems that the low sensitivity of validated Ab-RDT could only complement qRT-PCR in the detection of SARS-CoV-2 antibodies